1980
DOI: 10.1007/bf02408535
|View full text |Cite
|
Sign up to set email alerts
|

Electrical potential difference across bone membrane

Abstract: The control of ion fluxes to and from bone has important implications to mineralization and calcium homeostasis. Since ionic transport frequently results in an electrical potential difference across the layer of cells lining bone surfaces, knowledge of this potential is critical to understanding the means of regulation of ionic concentrations in the interior bone fluid phase. This work presents a determination of a metabolism-related electrical potential difference by a thermodynamic argument based on the dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…The existence of an electrochemical gradient at the BECF-ECF interface in viable bone was shown to depend on OBLCS viability (2,4,29,34,36). In fact, structural and ultrastructural analyses reported here clearly demonstrated that the osteocytes enclosed within the lacunocanalicular network and the bone lining cells (or osteoblasts) along the bone surfaces display a quite normal appearance in both unloaded and loaded metatarsals, thus confirming that all anatomical assumptions are correct.…”
Section: The Modelsupporting
confidence: 63%
“…The existence of an electrochemical gradient at the BECF-ECF interface in viable bone was shown to depend on OBLCS viability (2,4,29,34,36). In fact, structural and ultrastructural analyses reported here clearly demonstrated that the osteocytes enclosed within the lacunocanalicular network and the bone lining cells (or osteoblasts) along the bone surfaces display a quite normal appearance in both unloaded and loaded metatarsals, thus confirming that all anatomical assumptions are correct.…”
Section: The Modelsupporting
confidence: 63%
“…16 Aggregates of cells also set up voltages across various tissue layers, including cutaneous and corneal epithelium, vascular and intestinal walls, and the cortex and periosteum of long bones. 14,15,[17][18][19][20][21] These voltages are of the order of millivolts (mV) in magnitude, and where there is a conducting pathway they cause the movement of ions within tissue, constituting a bioelectric current, typically in the microamp (mA) range. 14 At the cellular level, bioelectricity is involved in the transport through the membrane of ions that can influence cell behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Since the tight junction is the most important barrier which restricts ion and water from passing freely through the paracellular space, the expression of tight junction proteins in osteoblasts supports the previous hypothesis that osteoblasts and bone-lining cells, which cover 90% of bone surface, form an epithelial-like bone membrane to regulate ion transport and maintain diVerential ion compositions between the plasma and BECF (Bushinsky et al 1989;Marenzana et al 2005;Peterson et al 1985;Trumbore et al 1980). Normally, concentrations of Ca 2+ , Mg 2+ and K + in BECF are approximately 0.5, 0.4 and 25 mM, whereas those in plasma are 1.25, 0.7 and 4.5 mM, respectively (Armstrong and Singer 1965;Trumbore et al 1980).…”
mentioning
confidence: 51%
“…Normally, concentrations of Ca 2+ , Mg 2+ and K + in BECF are approximately 0.5, 0.4 and 25 mM, whereas those in plasma are 1.25, 0.7 and 4.5 mM, respectively (Armstrong and Singer 1965;Trumbore et al 1980). These ionic gradients were thought to be actively maintained by bone membrane, and were dissipated in dead tissue or in the presence of inhibitors of ATP production (Marenzana et al 2005;Rubinacci et al 2002).…”
mentioning
confidence: 98%
See 1 more Smart Citation